Experimental Research of the Initial Temperature and Additives Effect on the Ignition and Combustion Mechanisms of Composite Liquid Fuel in a High-Temperature Oxidizer; Applied Sciences; Vol. 13, iss. 6 - Glushkov D. O. Dmitry Olegovich; Klepikov D. Dmitrii; Nigay A. G. Aleksandr Gerasimovich; Paushkina K. K. Kristina Konstantinovna; Pleshko A. Andrei (2023, 2023)
Title screen